2017
DOI: 10.5114/aoms.2017.71068
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of patients from rural and urban areas in Poland with head and neck cancer treated with radiotherapy. A study of the influence of selected socio-demographic factors

Abstract: IntroductionThe quality of life (QoL) experienced by cancer patients depends both on their state of health and on sociodemographic factors. Tumours in the head and neck region have a particularly adverse effect on patients psychologically and on their social functioning.Material and methodsThe study involved 121 patients receiving radiotherapy treatment for head and neck cancers. They included 72 urban and 49 rural residents. QoL was assessed using the questionnaires EORTC-QLQ-C30 and QLQ-H&N35. The data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The result also revealed that patients from urban areas were less likely to have a higher QoL. This was similar to a previous study assessing the QoL of patients from rural and urban areas, which showed that those living in big cities and metropolises had more considerable anxiety about the deterioration of their well‐being, compared to those in rural communities 60 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The result also revealed that patients from urban areas were less likely to have a higher QoL. This was similar to a previous study assessing the QoL of patients from rural and urban areas, which showed that those living in big cities and metropolises had more considerable anxiety about the deterioration of their well‐being, compared to those in rural communities 60 …”
Section: Discussionsupporting
confidence: 88%
“…This was similar to a previous study assessing the QoL of patients from rural and urban areas, which showed that those living in big cities and metropolises had more considerable anxiety about the deterioration of their well-being, compared to those in rural communities. 60 Our study suggests that an early individualized nutritional intervention during chemotherapy is feasible to improve the dietary intake as well as the QoL, especially among those prone to suffer from malnutrition and to report the worse QoL. High-protein intake should be recommended in order to enhance muscle mass and strengths, which positively affect the physical and role function and increase the overall QoL of cancer patients.…”
Section: Discussionmentioning
confidence: 80%
“…Second, although adequate validity and reliability have been shown for the FHSQ [12, 13, 22, 23], its reliability has not yet been established specifically for women who suffer from fibromyalgia and should be considered for future studies. Finally, quality of life could be modified according to socio-demographic factors such as the origin of women with fibromyalgia from rural or urban areas [39] as well as physical factors such as reduced bone mineral density [40].…”
Section: Discussionmentioning
confidence: 99%
“…QoL is an extensive and subjective construct [12] that "broadly encompasses how an individual measures the 'goodness' of multiple aspects of their life" [13]. The importance of studying healthrelated QoL in distinct health problems is widely recognized in previously published articles in this journal [14][15][16][17]. In old age this concept is even more important since it is commonly accepted that a shorter life with quality is better than a longer one without it [12].…”
Section: Introductionmentioning
confidence: 99%